An investigation into privacy and security in online social networking sites among IIUM students - Abdullahi, Husein Osman; Said, Abdirizaq; Ibrahim, Jamaludin (WCSIT, 2012)
the issues of privacy and security in online social networking sites have been the dual themes of utmost concern amongst many communities and IIUM community in particular. This article highlights the importance of online social networking sites such as: Face book, Google+, and Twitter and the issues of privacy and security in online interactions. The authors also argue that the online social networks have played a significant role on daily digital interaction for more than half billion users around the world today are bedeviling with the issues of privacy and security. This study employs a quantitative data analysis, a survey and a random sampling of (n=160) IIUM students from different Kulliyah were conducted. The result shows that the percentage responses of IIUM who seems to be actively involved in online social network pages are not aware of their privacy and security in online environment.